THE POPULATION STATUS OF PRIMATES IN THE UPPER AND LOWER PUTUMAYO BASIN, NORTHERN PERUVIAN AMAZON - DEL ÁGUILA-CACHI, Harvey Kuinsy Jonathan (2020)
Primates are fundamental to the regulation and regeneration of forests through the dispersion and predation of seeds. In addition, they act as indicators of ecosystem conservation, while some species are utilized for subsistence and commercialized as bush meat. For these reasons, the population status of primates was estimated in flooded forest and terra firme in the upper and lower Putumayo basin using the linear transect method. Ten primate species were detected over 838.8 kms of transect, nine of which corresponded to the upper basin and eight to the lower basin. Dominance was low among basins and habitats, while among locations; Nuevo Belén showed high dominance due to the abundance of Saimiri macrodon. The highest population densities corresponded to S. macrodon (14.69 ind./km2) and Leontocebus nigricollis nigricollis (7.83 ind./km2), and the lowest to Cebuella pygmaea pygmaea (0.04 ind./km2). We found a significant difference between habitats (ANOSIM, p= 0.001), where Leontocebus nigricollis nigricollis was abundant in flooded forest and Saimiri macrodon in the mainland. Correlation analysis indicates that there is a positive association between Pithecia napensis and Aloutta seniculus (p= 0.0004; r= 0.73). In conclusion, as the population densities of the large primates are low, it is necessary to implement conservation strategies according to the wildlife and native communities settled in this part of the Peruvian Amazon.